School terminology: Exploring the terminological apparatus of textbooks in natural and mathematical subjects - Nurgaliyeva, Saniya; Bolatov, Aidos; Akhmet, Akzhibek; Omarov, Sayat; Smakova, Danagul (International Journal of Innovative Research and Scientific Studies, 2025)
Textbooks on mathematics and natural science are two important contexts for using terminological vocabulary. Research and a thorough examination of these textbooks’ terminological apparatus appear pertinent given the variety of issues they develop, including theoretical, methodological, and cultural ones. Nevertheless, there has never been an evaluation of the apparatus of the terminology used in math and science textbooks. The study aims to evaluate the quality of the terminological apparatus in school textbooks covering natural and mathematical subjects. The questionnaire consisted of 12 items and covered terminological definition, clarity, supportive examples, etymology, and appropriateness of terms for students. The results showed that while the majority of teachers felt that the textbooks adequately defined new terms and provided helpful examples or illustrations, issues such as vague or misspelled definitions, inappropriate borrowed terms, and awkward pronunciation were also noted. Regression analyses revealed significant sociodemographic predictors of teachers’ responses, including experience, age, language of instruction, and qualification category. This study demonstrates the importance of thinking about the quality of the terminological apparatus in school textbooks covering natural and mathematical subjects. The findings highlight the strengths and weaknesses of the terminological apparatus in these textbooks, emphasizing the need for continuous improvement to enhance educational quality. Future research should explore psychological and pedagogical factors influencing students’ assimilation of terms, the role of terminological work in professional orientation, and strategies for improving the terminological literacy of future teachers.